Russian gas: the next ten years - Pirani, S (Oxford Institute for Energy Studies, 2012)
The way that Russia produces and markets natural gas will change substantially over the next decade. The main drivers of change may be grouped under four headings. First, production will shift geographically, away from its historical base in western Siberia. Second, the industry’s corporate make-up will change, with Gazprom losing share to others. Third, a related process, domestic market liberalisation, will probably be the most important determinant of change in the way that Russian gas is sold; a further decline in Russia’s share of the European market is a possible corollary. Fourth, while exports to Europe are likely to become less important, Russia will continue its long-standing endeavours to open up Asian markets. This article suggests ways that these four processes might play out, and offers some conclusions.